Islamic Banking Governance in Maqashid Sharia Perspectives: A Systematic Literature Review - Yenik Candra Kiranawati; Shifa Miarti Aziza; Arim Nasim; Caria Ningsih (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
The development of Islamic banking has prompted financial institutions to operate in accordance with Sharia principles. In this context, the role of sharia governance is crucial in supporting banking operations and enhancing bank performance. This study aims to examine the implementation of sharia governance in Islamic banking. To improve the performance of Islamic banks, good governance practices in line with Islamic law are essential, including the application of maqashid sharia principles. A library search was conducted using the Systematic Literature Review (SLR) method to analyze several national and international journal articles published in the past decade. Out of 75 identified articles, 38 were found to be relevant after screening. The results indicate that the implementation of Sharia governance can improve bank performance by adhering to the principles of Maqashid Sharia as a guide. Such implementation would enable Islamic banks to be leaders in the industry, enhance the quality of their services, and ultimately increase the company's value. This study concludes that adherence to the principles of Maqashid Sharia leads to higher bank performance in terms of service quality, which can improve a company's value. The implications of this study offer insights into how the implementation of Sharia governance, based on Maqashid Sharia principles, can affect bank performance in Islamic banking.========================================================================================================ABSTRAK – Tata Kelola Bank Syariah dalam Perspektif Maqashid Syariah: Suatu Kajian Literatur Sistematis. Perkembangan perbankan syariah telah mendorong lembaga-lembaga keuangan untuk beroperasi sesuai dengan prinsip syariah. Dalam konteks ini, peran tata kelola syariah sangat penting dalam mendukung operasional perbankan dalam meningkatkan kinerjanya. Penelitian ini bertujuan untuk mengkaji implementasi tata kelola syariah pada perbankan syariah. Dalam meningkatkan kinerja bank syariah, praktik tata kelola yang baik yang sejalan dengan konsep ekonomi Islam sangat penting, salah satunya dengan penerapan prinsip maqashid syariah. Pencarian data dilakukan dengan metode Systematic Literature Review (SLR) dengan menganalisis sejumlah artikel nasional dan internasional yang diterbitkan dalam satu dekade terakhir. Dari 75 artikel yang teridentifikasi, hanya 38 artikel yang relevan dengan topik kajian ini. Hasil kajian menunjukkan bahwa implementasi tata kelola syariah dapat meningkatkan kinerja bank dengan mengikuti prinsip Maqashid Syariah sebagai panduan. Implementasi tersebut juga memungkinkan bank syariah untuk menjadi yang terdepan dalam industri perbankan, meningkatkan kualitas layanan, dan meningkatkan nilai perusahaan. Kajian ini menyimpulkan bahwa penerapan prinsip Maqashid Syariah dalam operasional bank syariah dapat meningkatkan kinerja mereka dalam hal peningkatan kualitas layanan yang berefek pada peningkatan nilai perusahaan. Implikasi dari penelitian ini memberikan wawasan tentang bagaimana implementasi tata kelola syariah, berdasarkan prinsip Maqashid Syariah, dapat mempengaruhi kinerja bank syariah.